(untitled) (Spectrum Journal of Innovation, Reforms and Development, 2022)
The article presents a clinical case of a 37-year-old patient who was admitted to the hospital with signs of intestinal obstruction. During the diagnostic process, the cause of the obstruction was promptly detected - intestinal intussusception, which allowed avoiding complications in the form of intestinal necrosis, with the subsequent development of perforation and peritonitis. The proposed diagnostic and therapeutic algorithm justifies patients with intestinal intussusception, which improves the clinical outcome and reduces the risk of intra- and postoperative complications.